2005
DOI: 10.1090/s0025-5718-05-01768-0
|View full text |Cite
|
Sign up to set email alerts
|

Some heuristics and results for small cycles of the discrete logarithm

Abstract: Abstract. Brizolis asked the question: does every prime p have a pair (g, h) such that h is a fixed point for the discrete logarithm with base g? The first author previously extended this question to ask about not only fixed points but also two-cycles, and gave heuristics (building on work of Zhang, Cobeli, Zaharescu, Campbell, and Pomerance) for estimating the number of such pairs given certain conditions on g and h. In this paper we extend these heuristics and prove results for some of them, building again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…In [Holden 2002;Holden and Moree 2004;2006], heuristics and observed values for the number of small cycles (fixed points and two-cycles) in discrete exponentiation graphs are given. Our methods build on this to generate experimental data for the parameters described by the theoretical predictions in Section 3.…”
Section: Observed Resultsmentioning
confidence: 99%
“…In [Holden 2002;Holden and Moree 2004;2006], heuristics and observed values for the number of small cycles (fixed points and two-cycles) in discrete exponentiation graphs are given. Our methods build on this to generate experimental data for the parameters described by the theoretical predictions in Section 3.…”
Section: Observed Resultsmentioning
confidence: 99%
“…considered (with e = 1) in [15] as closely related to (3). Another problem that should be tractable using our methods is finding solutions of (11) g x−1+c ≡ x mod p e for c fixed.…”
Section: Discussionmentioning
confidence: 99%
“…A related conjecture by Holden and Moree [236] states that one should have F (p) = (1 + o (1))p. Bourgain et al [44] showed that F (p) = p + O(p 4/5+ǫ ) for a set of primes p of relative density 1 and in a later paper, [45],…”
Section: )mentioning
confidence: 98%
“…Let F (p) denote the number of pairs (g, h) satisfying g h ≡ h(mod p) with 1 ≤ g, h ≤ p − 1. Let G(p) denote the number of pairs (g, h) satisfying g h ≡ h(mod p) with 1 ≤ g, h ≤ p − 1, where in addition we require g to be a primitive root modulo p. Holden and Moree [236,Conjecture 8.3] …”
Section: )mentioning
confidence: 99%